A Conclusion, Yet an Opening to Enriching the Normative Approach of Culture - CHIU, Chi-Yue (Institutional Knowledge at Singapore Management University, 2015)
We compile in this article the target article authors’ thoughtful responses to the commentaries. Their responses identify some common threads across the rich contents of the commentary pieces, interlink the observation and theoretical propositions in the commentaries with broader streams of research, present new perspectives inspired by the commentary contributors, and pose provocative questions to further ignite research efforts on the normative analysis of culture.